Latvia - From Exuberance to Prudence : A Public Expenditure Review of Government Administration and the Social Sectors - Overview and Summary - World Bank (World Bank, 2012)
This public expenditure review (PER) was conducted at the request of the Ministry of Finance (MoF) on behalf of the Government of the Republic of Latvia. The objective of the PER is to identify potential areas of further budget savings in public administration and the social sectors that could help restore fiscal balance, speed Latvia's recovery from the current crisis, and help it to meet the Maastricht Criteria by 2012 so it can adopt the Euro in 2014. The remainder of this volume is structured in the following way. Section two recounts the events and circumstances that set the Government's fiscal stance in the years prior to the crisis. Section three summarizes the principal emergency measures the Government took to cope during 2008 and 2009 as the crisis broke and led to Latvia's severe economic contraction. The purpose of these sections which draw liberally from material prepared by the financial authorities, the International Monetary Fund (IMF) and the European Central (EC) is to make the case for further fiscal adjustment plain. The report then summarizes the main messages and highlights the most important suggestions made in each of the longer, more detailed chapters of volume two of the review. Each section is followed by a matrix of the options presented for the Government to take into consideration. Given the important role that municipalities and republican cities play in the delivery of social services, the chapter three of volume two provides an in depth examination of local government finances and spending. Local authorities (municipalities and republican cities) play such a prominent role in the delivery of public services particularly social services that a close look at the character of their spending is critical.